The Effect of Self Organized Learning Environments (SOLE) Approach on Student's Learning Motivation and Achievement in History Lessons - Satriani, Ani; Umar, Umar; Fahlia, Fahlia (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
Crisis education going on Indonesian people now this cause worries, especially for parents and party schools that have trusted as institution education. When Indonesia was hit by the covid pandemic – 19 in the middle March 2020, students study from distance far away (PJJ), and this PJJ the more add crisis education in Indonesia. Study this aim for knowing influence motivation and performance study student to approach learning self organized learning environments (SOLE) at eye lesson history in class X SMAN 1 Sumbawa Besar. This study is a quantitative descriptive study. The type of data used, namely primary data obtained from the deployment questionnaire results to the participants educate. The sample in study are 74 respondents who are participant educate class X majors Knowledge Knowledge Social Studies (IPS) at SMAN 1 Sumbawa Besar Year Lesson 2021/2022. The data analysis method used is multiple linear regression which includes test data quality, test assumption classic, test partial, test simultaneous, and test coefficient determination. Results study show that the application approach to learning self organized learning environments (SOLE) implemented at SMAN 1 Sumbawa Besar is welcome good by students or participants educate, and approach learning self organized learning environments (SOLE) can be an increase in motivation and performance of study students. Besides that, ability variable free in explain variable bound based on score Adjusted R Square by by 81%, the remaining 19% is explained by other variables that are not researched and no discussed in this study.